Short‐term decline of Castanopsis fargesii adult trees promotes conspecific seedling regeneration: The complete process from seed production to seedling establishment. Issue 19 (9th September 2020) - Huang, Li; Zhou, Lihua; Wang, Jingmei; Jin, Cheng; Hu, Siwei; Qian, Shenhua; Lin, Dunmei; Zhao, Liang; Yang, Yongchuan
Abstract: Declining forests usually face uncertain regeneration dynamics and recovery trajectories, which are challenging to forest management. In this study, we investigated the decline pattern of Castanopsis fargesii and examined the effects on conspecific seedling regeneration. We found that 61.45% of adult individuals were in decline and the smaller DBH size classes of trees (10–40 cm) had a greater probability of decline. Most of the intermediate decline (94.52%) and nondecline individuals (95.23%) did not worsen, and the crowns of 21.91% of the intermediate decline trees were recovered during 2013–2018. Adult tree decline had a negative effect on seed production (mean mature seed density of nondecline, intermediate decline, and high decline individuals was 167.3, 63.3, and 2.1 seeds/m 2, respectively), but no effect on key seed traits. The seed survival rate of declining trees was greater than that of nondeclining trees at both the seed production and seed dispersal stages. The seed to seedling transition rates in canopy gaps, decline habitats, and nondecline habitats were 7.94%, 9.47%, and 109.24%, respectively. The survival rate and height growth of newly germinated seedlings were positively correlated with the light condition, which was notably accelerated in the canopy gaps. Taken together, these results indicate that the reduction in seed production of some adult trees had a weakly negative effect on new seedling recruitment, while the improved environmental condition after the decline significantly enhanced the survival and growth of both advanced and new germinated seedlings. Looking at the overall life history, the short‐term defoliation and mortality of some C. fargesii adult trees can be regarded as a natural forest disturbance that favors conspecific seedling regeneration. High‐intensity management measures would be unnecessary in cases of an emerging intermediate decline in this forest. Abstract : The reduction in seed production of some adult trees caused by decline had a weakly negative effect on new seedling recruitment, while the improved environmental condition after the decline significantly enhanced the survival and growth of both new and advanced seedlings. Looking at the overall life history, the short‐term defoliation and mortality of some Castanopsis fargesii adult trees can be regarded as a natural forest disturbance that favors conspecific seedling regeneration.